ALBI and Child-Pugh score in predicting mortality in chronic liver disease patients secondary to alcohol - A retrospective comparative study - Nagaraja, B S; Madhumathi, R; Sanjeet, S B; Umesh, K J; Nandish, S Kumar (Asian Journal of Medical Sciences, 2019)
Background: The severity of liver dysfunction in chronic liver disease is often estimated with Child-Pugh (CTP) classification or model for end-stage liver disease (MELD) score. The albumin-bilirubin (ALBI) score is a new model for assessing the severity of liver dysfunction, which is simple and more objective. Aims and Objective: The present study was aimed to retrospectively compare the performance of ALBI score with Child-Pugh score for predicting the mortality in patients with chronic liver disease. Materials and Methods: Data of patients with chronic Liver disease irrespective of etiology were retrospectively reviewed. Child Pugh score and ALBI score were calculated for the patients and results from ROC curves were analysed. Results: Study conducted on 299 patients of chronic liver disease, age distribution was between 20-85 years with mean age of patients being 45.7+/-10.94 years, sex ratio male: female is 265:34 with mortality rate of 19.73%.The area under curves of ROC of ALBI and Child pugh are 0.586 and 0.549 respectively. Conclusion: Ability of ALBI score for predicting mortality was comparable with that of Child Pugh score but Child pugh score of more than 10 has got better performance of predicting mortality as compared to ALBI score.